SARS-CoV-2 organising pneumonia: ‘Has there been a widespread failure to identify and treat this prevalent condition in COVID-19?’ - Pierre Kory; Jeffrey P Kanne (BMJ Open Respiratory Research)
Reviews of COVID-19 CT imaging along with postmortem lung biopsies and autopsies indicate that the majority of patients with COVID-19 pulmonary involvement have secondary organising pneumonia (OP) or its histological variant, acute fibrinous and organising pneumonia, both well-known complications of viral infections. Further, many publications on COVID-19 have debated the puzzling clinical characteristics of ‘silent hypoxemia’, ‘happy hypoxemics’ and ‘atypical ARDS’, all features consistent with OP. The recent announcement that RECOVERY, a randomised controlled trial comparing dexamethasone to placebo in COVID-19, was terminated early due to excess deaths in the control group further suggests patients present with OP given that corticosteroid therapy is the first-line treatment. Although RECOVERY along with other cohort studies report positive effects with corticosteroids on morbidity and mortality of COVID-19, treatment approaches could be made more effective given that secondary OP often requires prolonged duration and/or careful and monitored tapering of corticosteroid dose, with ‘pulse’ doses needed for the well-described fulminant subtype. Increasing recognition of this diagnosis will thus lead to more appropriate and effective treatment strategies in COVID-19, which may lead to a further reduction of need for ventilatory support and improved survival.